Impacto do serviço de polinização para segurança alimentar do PNAE na microrregião de Limeira - Domingos, Sara Stefani (Universidade Federal de São Carlos, 2023)
Nature's Contributions to People (NCP) cover a wide range of human-nature interactions that provide basic life support, material and non-material goods for humanity, and can be evaluated by quantifying the benefits provided by ecosystems as an incentive for their preservation. Pollination is the most studied NCP worldwide, as it contributes to 35% of global food production, providing food security with the diversity of foods with important nutritional value. In this sense, foods dependent on the pollination service can be an important source of nutrients for children and adolescents in the learning phase. In school meals provided by the National School Feeding Program (PNAE), agricultural products make up an adequate menu in nutritional terms, and the diversity of these foods may be related to the pollination service. Therefore, the objective of this work was to identify the dependence of the pollination service on food provided for school meals in public schools in the Limeira microregion and to estimate the economic value of this pollination service. The database was built with information from invoices for purchases made within the scope of the PNAE for eight municipalities belonging to the microregion. The results showed that 49% of fresh or minimally processed foods depend to some degree on the pollination service and the economic value of this service was estimated at around one million reais. It is concluded that there was an impact of the pollination service on school meals in the Limeira micro-region, promoting food security and helping family farmers in the micro-region in the diversified production of agricultural products rich in nutrients. More studies in this sense can be carried out to assist decision makers in creating public policies to protect pollinators.
Impact of the PNAE pollination service on food security in the Limeira microregion
Keywords: Serviços ecossistêmicos; Agricultura familiar; Alimentação escolar; Diversidade nutricional; Escolas públicas; Ecosystem services; Family farming; School feeding; Nutritional diversity; Public schools; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS DA SAUDE::NUTRICAO; CIENCIAS HUMANAS::EDUCACAO